A Proinflammatory Effect of the β-Glucan from Pleurotus cornucopiae Mushroom on Macrophage Action. (15th May 2017) - Minato, Ken-ichiro; Ohara, Akihiro; Mizuno, Masashi
Abstract : PCPS from P. citrinopileatus mushroom extract is a β -1, 6-glucan possessing a proinflammatory effect on innate immune cells. The PCPS stimulated THP-1 macrophages to secrete significant levels of TNF. Moreover, the mRNA expressions of TNF and IL-1 β were significantly enhanced by PCPS treatment. However, the PCPS did not induce to express both IL-12 and IL-10 mRNA in the macrophages. Next, the P. cornucopiae extract (containing mainly PCPS) treatment against mice showed significant increases in TNF and IL-1 β mRNA expressions in the peritoneal macrophages of them. In this study, the expression levels of IFN γ mRNA in the spleen were almost the same between the extract- (PCPS-) treated group and control group. However, the expression of IL-4 mRNA showed a lower level in the extract-treated group than that in the control. Our results suggested that the PCPS could induce proinflammatory action in the immune response. In addition, the proinflammatory effect of the PCPS on THP-1 was enhanced by 5′-GMP-Na, while it was reduced by vitamin D2 . These two compounds are majorly contained in the P. citrinopileatus mushroom. Therefore, these results suggested that the P. citrinopileatus mushroom might contain other immune regulative compounds, such as vitamin D2, as well as PCPS.